Analisis Pengaruh Variasi Media Pendingin Terhadap Sifat Mekanik dan Laju Korosi Pada Hasil Sambungan Las TIG Baja ST 37 - Muhammad Fadli Rahman; Viktor Naubnome; Rizal Hanifi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The construction of metal construction nowadays involves a lot of welding elements, especially in the field of design, but corrosion of metal has a bad impact on welded joints, including a decrease in the strength of the material and damage to the construction. The quenching heat treatment process is also a major factor that greatly influences changes in mechanical properties due to phase changes. This study aims to improve the mechanical properties of construction steel type ST 37 on GTAW welding results with oil cooling media SAE 15W-40, coconut oil and without cooling media (free air). The results showed that the highest hardness test was found in coconut oil cooling media worth 244.4 HV than SAE-40 oil cooling media, coconut oil, without cooling media and raw materials. The lowest corrosion rate value is found in the SAE 15W-40 oil cooling medium worth 0.3545 mmpy compared to other cooling media (.coconut oil, without cooling media) and raw materials.